Study of Building Facade in Fishing Industries - Luqman Nashirudin Nafiq; Satriya Wahyu Firmandhani (Journal of Architectural Design and Urbanism, 2021)
Many industrial buildings are growing in Indonesia, one of them being the fishing industry. However, the industry has a monotonous and rigid facade. The facade is an essential element that makes the first impression. This study aims to evaluate how the facade of an ideal industrial building, especially in the fishing industry. The method used is descriptive qualitative on the several parameters of façade design. The results of the study are in the form of an evaluation and guidelines of the ideal facade, in terms of visuals, functions, and the requirements.